2020
DOI: 10.14245/ns.1938308.154
|View full text |Cite
|
Sign up to set email alerts
|

Opioids and Spinal Cord Stimulators: Pre- and Postoperative Opioid Use Patterns and Predictors of Prolonged Postoperative Opioid Use

Abstract: The aim of the study was to compare trends and differences in preoperative and prolonged postoperative opioid use following spinal cord stimulator (SCS) implantation and to determine factors associated with prolonged postoperative opioid use. Methods: A database of private-payer insurance records was queried to identify patients who underwent a primary paddle lead SCS placement via a laminectomy (CPT-C3655) from 2008-2015. Our resulting cohort was stratified into those with prolonged postoperative opioid use, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…In this retrospective analysis, at nearly all time points and for both “responder” status thresholds, a history of chronic opioid use at the time of implant was associated with a statistically significant likelihood of “nonresponder” status. This is concordant with prior studies in neuromodulation, demonstrating that prior pre‐procedural opioid use generally correlated with worse clinical efficacy outcomes (26,27). This association also transcends to the chronic pain population undergoing other interventional procedures that does not involve neuromodulation (23).…”
Section: Discussionsupporting
confidence: 89%
“…In this retrospective analysis, at nearly all time points and for both “responder” status thresholds, a history of chronic opioid use at the time of implant was associated with a statistically significant likelihood of “nonresponder” status. This is concordant with prior studies in neuromodulation, demonstrating that prior pre‐procedural opioid use generally correlated with worse clinical efficacy outcomes (26,27). This association also transcends to the chronic pain population undergoing other interventional procedures that does not involve neuromodulation (23).…”
Section: Discussionsupporting
confidence: 89%
“…Importantly, SCS can reduce pain severity sufficiently to allow some pain patients to reduce their use of medications and break free of opioid dependence. 8,9 A landmark randomized controlled trial comparing SCS with conventional medical management showed that the former provided better leg pain relief, quality of life, and functional capacity and could be sustained through 24 months. 10 In the last decade, innovations in SCS have led to the development of new electrical waveforms.…”
Section: Introductionmentioning
confidence: 99%
“…However, they are more favorable than a database review involving 2374 patients who underwent SCS paddle lead placement for a variety of different indications including PLS, radiculopathy, and lumbago, that actually reported an increase in post-implant opioid consumption in 5 of the 8 years analyzed (with no statistical difference in the other 3 years). 20 In this study, no pain comorbidity was significantly associated with a greater likelihood of reducing opioid consumption, and the criteria for defining preand postsurgical opioid consumption were more liberal than ours. It is important to note that there are no clinical trials evaluating pure mu opioid agonists for PLS in a nonaddicted population, and that opioids may exacerbate central sensitization in those who fail spine surgery with nociplastic, nonspecific spinal pain.…”
Section: Comparison With Other Studiesmentioning
confidence: 51%